Jealousy and Novelistic Knowledge - DiBattista, Maria (Mimesis, desire, and the novel, 2015)
In the repertoire of emotions that fascinate, when they do not dismay, René Girard, jealousy occupies a preeminent and ultimately fateful place. In Deceit, Desire, and the Novel Girard identifies jealousy as one of the "vices" of internal mediation and seconds Stendhal’s warning against jealousy as one of the distinctly " modern emotions."¹ As this formulation suggests, jealousy for Girard is less a moral failing than a symptom of an ontological sickness endemic to the spiritual culture of modernity. According to his diagnosis, the jealous lover disguises the true nature of his affliction by attributing all his sufferings to a possessive